Sistema linear óptico para protótipo de detector de fumaça - Santos, Wendell Cristian Ferruccio dos (2016)
Since the beginning of history, the discovery and control of fire, brought evolution to humans. Even though fire control brings evolution, the uncontrolled fire leads to loss of lives and destroys property. Having said that the instinct to protect yourself is always present in the mankind, it's important to emphasize that reducing costs for this kind of system might make it increasingly available for all sorts of business. For that reason, the objective of this paper is to develop an optical linear smoke detector prototype, which is able to identify different levels of smoke and trigger audible and visual emergency signals. Thus it will be much easier to combat the source of fire. It is based on a linear detection system where a large sensing area can be performed with on detector. Its development was divided into two parts. Firstly a signal module that operates through a circuit sending and receiving. Secondly the treatment module was developed with an AT89S52 microcontroller which processes the data sent by the receiver. Thus to carry out the activation of the emergency signals. The result of this work is a linear smoke detector prototype with a range of 17 meters with an intuitive alignment system and is able to detect different levels of smoke in accordance with the firmware recorded in its EPROM.